Water Level Control Monitoring Based On Arduino Uno R3 Atmega 238p Using Lm016l LCD at STMIK Hang Tuah Pekanbaru - Wahyuni, Refni; Sentana, Jeri Trio; Muhardi, Muhardi; Irawan, Yuda (Journal of Robotics and Control (JRC), 2021)
Water plays an important role in the survival of living creatures on earth. The advancement of computerized technology encourages people to make appropriate equipment that can be utilized in various aspects of life, such as ease in controlling the performance of water pumps in the shelter. STMIK Hang Tuah Pekanbaru uses system level switch but there are some weaknesses also in this system level switch that pump will live more than 1 time a day if there is damage to the buoy. In this study will be made a tool that can do the monitoring water height automatically. "Monitoring Water Level Control Arduino Uno using LCD Lm016l" which is able to monitor and control the water level in the Tandon using ultrasonic sensors. The working principle of the appliance is that if the water reservoir is empty or reaches the 20% level, the ultrasonic HC-SR04 sensor will detect the water level and give signal to arduino uno to switch the water tank filler pump and send the water level data to the LCD. If the water reservoir is in full condition or reaches the 100% level, the ultrasonic HC-SR04 sensor will detect the water level and give signal to arduino uno to automatically turn off the automatic water supply pump and transmit the water level data on the LCD, making it easier to control the inventory water.